The Entrance to Trabzon from East Gate: Tabakhane and Ortahisar - Gerçek Atalay, Neva; Karakaş, Bahar (ICONARCH International Congress of Architecture and Planning, 2017)
The city of Trabzon, was established on a plenary hillside which remains in between Tabakhane and Zağnos valleys horizontally. In resources, it is mentioned that the first usage of the city’s name was “Trapezus” which means “table” and this usage was a result of the city’s position, since it is established on a decent hillside which rises between two valleys. The east border of the study, which is the East Gate (Tabakhane Gate) of the historical walls, is important as it is the entrance point to the city through “Gavur Square”, which became the second centre of the city in time. The west border (Fatih Grand Mosque) of the study is also important since it is the oldest church of the city and it was the first example which was transformed into mosque due to Ottoman conquest procedures after the city was conquered by Fatih Sultan Mehmet. The border of the study is determined as the curled artery, which continues between these two historical elements and the public, and civil architectural examples in the artery from Tabakhane Mosque and Bridge to Fatih Grand Mosque are studied with a framework of historical chronology. In the first phase of the study, brief information about the history of Ortahisar is composed and data about the historical structures in the determined area (Tabakhane Gate, Bridge and Mosque, Ortahisar and Old Government House, Fatih Grand Mosque) are compiled. In the second phase of the study, the space between the city’s east gate (Tabakhane Gate) and the Fatih Grand Mosque (Panaghia Chrysokephalos Church), which is one of the most important sacred structures, transformed from church and still exists today, is evaluated by comparing the oldest photos that can be reached, archive documents from the Directorate of Cultural and Natural Heritage Conservation Board in Trabzon region, historical plans and the recent photos that are taken from close points. Evaluation of the subject is made through legal regulations, conscious of protection and Architectural approach. With this study, it is shown that how the area, which is determined as a 2nd degree urban protected area, exposed to interventions in the historical context. The evolution of the consciousness of protecting history in Ortahisar, the oldest centre of the city, from Republic to today, is analysed and argued. In the conclusion of the study, it is evaluated how the historical urban fabric of Trabzon resist towards deformations and illegal structuring, in the historical continuity. Interventions to historical fabric, violation of the legal borders and unqualified spots mixed in the historical memory in an urban protected area are emphasised. Upon the light of the consequences that are reached, the study aims to contribute to the architectural protection conscious, and to set an example for studies of city history and protection in local/regional means.